How a generally well-accepted measles vaccine mandate may lead to inequities and decreased vaccine uptake: a preregistered survey study in Germany - Julia Neufeind; Nora Schmid-Küpke; Eva Rehfuess; Cornelia Betsch; Ole Wichmann (BMC, 2022)
Abstract Background In Germany, a measles vaccine mandate came into effect in March 2020, requiring proof of measles immunization for children attending kindergarten or school and for staff in a variety of facilities. Mandates can be successful if implemented with care and in a context-sensitive manner. They may, however, also lead to inequities and decreased uptake of other vaccines. The aim of this study was to investigate the acceptance and potential unintended consequences of the measles vaccine mandate in Germany. Methods As part of a larger evaluation project on the new mandate, we conducted an online survey among parents in August/September 2020. We assessed differences in knowledge about the mandate and the measles vaccine by socio-economic status. We used linear and logistic regression to estimate how reactance to the mandate was associated with vaccination status and vaccination intention against other diseases. We used mediation analysis to measure how trust in institutions had an impact on the attitude towards the mandate, mediated by level of reactance. Results In total, 4,863 parents participated in the study (64.2% female, mean age = 36.8 years). Of these, 74.1% endorsed a measles vaccine mandate for children. Parents with lower socio-economic status had less knowledge about the mandate and the measles vaccine. The higher parents' levels of reactance, the lower the vaccination intentions and the likelihood for the child to be vaccinated against other diseases. Furthermore, higher institutional trust decreased the level of reactance and increased positive attitudes towards the mandate (partial mediation). Conclusions The new measles vaccine mandate in Germany, though well accepted by many, might have unintended consequences. Parents with lower socio-economic status, who know less about the mandate and vaccine, might be less likely to comply with it. The mandate may also lead to some parents omitting other childhood vaccines, as a way to restore their freedom. This could decrease vaccination coverage of other vaccines. Any potential loss of trust might provoke more reactance and lower acceptance of mandates. Policymakers should now expand communication activities on the mandate, monitor trends in vaccination coverage carefully and take measures to strengthen trust.